All you can eat: greed, lust, and the new capitalism - McQuaig, Linda (Penguin, 2001)
Explains the mired history of social and economic thinking that has culminated in the new capitalism. McQuaig argues that instead of shaping our society to fit the economy, we must shape the economy to fit the society we want. 2001.
Economics
Keywords: business & economics; capitalism; capitalism - history; economic history; free enterprise; political science